Salinization effects on coastal terrestrial and freshwater ecosystems - Venâncio, Cátia Alexandra Ribeiro (2017)
The projections made by the International Panel on Climate Changes (IPCC) until the year 2100 foresee scenarios of increased sea level rise and extreme weather events. As a consequence of these changes it is anticipated that coastal ecosystems (both terrestrial and freshwater) will suffer from seawater (SW) intrusions and, consequently, become impacted with salinization. Such salinization, caused by SW intrusion, may occur through surface flooding (for example due to violent storms, which may lead to pulses of SW intrusion with high peaks of salinity that, most probably, will cause lethal effects on biota) and/or groundwater intrusion (which may occur more gradually, and, most likely starts by inducing sublethal effects in the ecological receptors). In this context, the present work intended to evaluate the adverse effects that salinization, due to SW intrusion, may cause to coastal ecosystems. For this, several specific goals were identified: (i) to determine if sodium chloride (NaCl) may be used as a surrogate of SW at early stages of ecological risk assessment frameworks. This possibility would be advantageous since many toxicity data exist for NaCl and, therefore, it would reduce the number of toxicity assays needed to be carried out; (ii) to identify the ecological receptors most sensitive to salinization, by using standard approaches; (iii) to establish if biota is capable of acquire an increased tolerance to low levels of salinization through mechanisms of phenotypic plasticity; (iv) to assess the effects of increased salinity on interspecies relationships; and (v) to identify the effects of salinization for freshwater and soil communities under realistic exposure scenarios. These objectives were addressed along seven chapters by using standard and non-standard ecotoxicological approaches from the individual (by exposing organisms, from species belonging to different trophic levels, to increased salinity levels) to the community level (by performing multispecies exposures under more realistic scenarios of exposure). Obtained results revealed that, in general, NaCl exerted a similar or higher toxicity than SW, both to freshwater and terrestrial species. These results, suggest that NaCl could be used as a surrogate of SW at early stages of ecological risk assessment of salinization caused by SW intrusion. However, caution must be taken since there were a few species for which SW revealed higher toxicity, and multigenerational exposures showed an increase in the sensitivity to SW for microalgae species. Within the freshwater compartment, cladocerans and rotifers were the two taxonomic groups exhibiting the highest sensitive to salinization (both for NaCl and SW) while fish and macrophytes showed to be the most tolerant groups. Ecotoxicity data obtained for terrestrial plants and fungi (generated in the present work) was integrated with data obtained from literature, allowing to identify microinvertebrates (Folsomia candida and Enchytraeus crypticus) as the most sensitive group to salinization while fungi and plants were the most tolerant ones. The toxicity data generated from standard assays (or in part compiled from literature for terrestrial species) was used to compute the hazard concentrations that allowed protecting 95% of species (HC5), on the basis of species sensitive distribution curves. The values of HC5 were computed for freshwater and terrestrial species and for NaCl and SW; all of these values were very low (HC5 ≤ 2.26 mScm-1) when compared to the conductivity of natural seawater (≈ 52 mScm-1), foreseeing that coastal ecosystems will be at a high risk due to salinization. Experiments involving a pre-short and long-term (multigerational) exposure to low levels of salinity, overall, did not caused a change in the tolerance of biota to this stressor. However, some species revealed an increased tolerance (either associated with physiological acclimation or other mechanisms of phenotypic plasticity) to salinity after short (the amphibian species Pelophylax perezi) and multigenerational exposure (the cyanobacteria Cylindrospermopsis raciborskii and the cladoceran Daphnia longispina) to low levels of salinity. Contrarily to this, it was also observed that a few species revealed a higher sensitivity to salinization after multigenerational exposure (the microalgae Raphidocelis subcapitata and the macrophyte Lemna minor). These diverse results may be due to differences in the intensity of salinity stress and to the duration of the periods of exposure to low levels of salinization. To more accurately understand the influence of prolonged exposure to low levels of salinity in biota tolerance to this stressor, further studies should be carried out involving multigenerational exposure to sublethal levels of salinization. Regarding the specific objective (iv), the obtained results revealed that sublethal salinization levels influenced interspecific relationships. For freshwater microalgae, it was observed that, at low levels of salinity, a shift in the competition between the two microalgae species occurred. Adding to the direct effect that these changes will caused in the structure of microalgae community, indirect effects on other species (e.g. cladoceran species that feed on them) are also foresee. For terrestrial plants in the absence of salinization, a lower productivity was registered for some tested plants when exposure occurred under polyculture conditions comparatively to monoculture conditions. However, exposure to the salinity threshold of 4 mScm-1 under such conditions seemed not to alter the pattern of responses. Finally, exposure under more realistic scenarios (outdoor mesocosms) suggested a much lower toxicity of salinization to freshwater ecosystems than that predicted from standard approaches, suggesting a higher resilience of communities to salinization under more complex and relevant scenarios of exposure. These results suggest that risk of salinization to freshwater ecosystems may be overestimated when using standard methodologies and that ecologically relevant scenarios at higher stages of ecological risk assessment for this stressor should be considered.